The role of institutional logics during participation in urban processes and projects: Insights from a comparative analysis of upgrading fifteen informal settlements in Kenya - Wainaina, George Kiambuthi; Truffer, Bernhard; Lüthi, Christoph (Elsevier Ltd, 2022)
The academic literature largely acknowledges participation as a key condition for the successful upgrading of informal settlements. However, how individual participative actions of different actor groups and reactions of dwellers combine to influence project outcomes of upgrading processes has not been studied. This article posits that different combinations of presence or absence of collaborative interactions between dwellers and other actors will decisively predict the success and failure of projects. Specifically, we argue that interactions between different groups of implementers and dwellers are conditioned by distinctive value systems—institutional logics—, which provide specific challenges to establishing collaborative interactions with dwellers as the actors conduct their roles. We identify sufficient combinations of participative actions that may lead to successful upgrading using qualitative comparative analysis (QCA) on 15 informal settlements in Kenya's secondary towns that were recently upgraded. Our findings indicate that participation has to consider a multiplicity of actors, who are guided by different logics; it has to span over the whole implementation cycle. It also has to deal reflexively with the issue of representation of the community. This extends the understanding of participation to a perspective that emphasizes the capabilities of implementers to enact collaborative relationships by bridging between their own and the community's institutional logic.
Keywords: Informal settlement upgrading; Institutional logics; Kenya; Participation; Qualitative comparative analysis; Development; Sociology and Political Science; Urban Studies; Tourism, Leisure and Hospitality Management